To Compare the Diagnostic Accuracy of CRP with Blood Culture In Neonatal Sepsis: A Prospective Study - Dr. Shruti Sharma; Dr. Kiran Meena; Dr. Ashish Pareek (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Neonatal sepsis is a leading cause of morbidity and mortality in newborns. Early diagnosis remains challenging due to nonspecific clinical signs. Blood culture is the gold standard but has limitations, including delayed results. C-reactive protein (CRP) is an acute-phase reactant that may aid in early diagnosis. Objective: To compare the diagnostic accuracy of CRP with blood culture in neonatal sepsis. Methods: A prospective study was conducted on 48 neonates with suspected sepsis. CRP levels were measured at admission, and blood cultures were performed. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of CRP (cutoff ≥10 mg/L) were calculated against blood culture. Results: Blood culture was positive in 18/48 (37.5%) cases. CRP showed a sensitivity of 83.3%, specificity of 76.7%, PPV of 71.4%, and NPV of 86.2%. The agreement between CRP and blood culture was moderate (κ = 0.58). Conclusion: CRP is a valuable adjunct to blood culture in neonatal sepsis, offering rapid results with reasonable accuracy. Combining both tests may improve early diagnosis and treatment.